Energy paradoxes - Madureira, N. L. (Frontiers in Energy Research, 2021)
In the domain of energy systems, paradoxes show that history runs often against what is expected or predicted. This article reviews the paradoxes related with the transition from wood to coal, and then from coal/oil to nuclear, and concludes by lifting a corner of the veil on the paradoxes that have already surfaced in the transition from fossil fuels to renewable energy (green paradoxes).